Alkylated indacenodithieno[3,2-b] thiophene-based all donor ladder-type conjugated polymers for organic thin film transistors - Lu,R; Han,Y; Zhang,W; Zhu,X; Fei,Z; Hodsden,T; Anthopoulos,TD; Heeney,M (Journal of Materials Chemistry C, 2018)
We report the synthesis of a series of indacenodithieno[3,2-b]thiophene (IDTT) based conjugated polymers by copolymerization with three different electron rich co-monomers [thiophene (T), thieno[3,2-b] thiophene (TT) and dithieno[3,2-b:2′,3′-d]thiophene (DTT)] under Stille coupling conditions. The resulting all-donor polymers show very good solubility in common solvents and exhibit similar optical, thermal and electronic properties. However, the performance of these semiconductors in thin film transistor devices varied and was highly dependent on the nature of the co-monomer. All polymers exhibited unipolar p-type charge transport behaviour, with the mobility values following the trend of IDTT-TT > IDTT-DTT > IDTT-T. The peak saturation mobility value of IDTT-TT was extracted to be 1.1 cm 2 V -1 s -1 , amongst the highest mobility for all-donor conjugated polymers reported to date.